Critical geographies of sport: space, power and sport in global perspective - Koch, Natalie (Routledge, Taylor &Francis Group, 2017)
pt. 1. Sports, geopolitics, and state space -- pt. 2. Sports, community, and urban space.
Keywords: Aufsatzsammlung; Politik; Stadtsoziologie; Sportsoziologie; Anthropogeografie; Sport